TEENAGE PERCEPTION TOWARDS THE ROLE OF BEAUTY VLOGGER IN THE EFFORT TO DEVELOP BUYING INTEREST - Widiastuti, Tuti (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
Youtube is a popular video sharing website where users can load, watch and share video clips in a free way. Generally videos on YouTube are music video clips, movies, TV, and videos made by Youtubers. The video that is popular by teenagers, especially young women, is the vlog content of makeup tutorials or review makeup by beauty vlogger. Currently the cosmetics industry believes the YouTube Beauty Vlogger to review its products through vlog content. One of them is Emina cosmetic product that trusts Abel Cantika, a YouTube beauty vlogger as a Celebrity Endorser for its products. This study uses the theory of mass communication and the theory of perception regarding the buying interest on a product. The purpose of this study is to examine more deeply the role of beauty vlogger in influencing buying interest in teenagers on Emina cosmetics. This study used a qualitative research method with data obtained through interviews with three informants who are teenagers in terms of age 17- 20 years old. The results of the research of the three informants showed that the role of beauty vlogger greatly influenced the buying interest in Emina products. To cite this article (7th APA style): Widiastuti, T. (2019). Teenage Perception towards the Role of Beauty Vlogger in the Effort to Develop Buying Interest. Journal Communication Spectrum, 9(1), 1-13. http://dx.doi.org/10.36782/jcs.v9i1.1924